НАРИЙН СУХАЙТЫН ОРДЫН НҮҮРС АГУУЛАГЧ ЭЛСЭН ЧУЛУУНЫ НАЙРЛАГА, ХУРИМТЛАЛЫН ОРЧИН - Н., Байгалмаа; Д., Нансалмаа; Л., Жаргал; Б., Эрдэнэцогт; Д., Алтанцэцэг; А., Баатархуяг; М., Номинцэцэг (Geological Issues, 2022)
Seven sandstone samples were collected from Middle Jurassic Orgilokhbulag Formation distributed at Nariinsukhait coal deposit and petrographical study has been completed. According to the results of study, the sandstones are classified into subarkose, sublitharenite and feldspathic litharenite. The sandstone provenance analysis suggests that the sandstones were deposited during the late stage of development of Noyon syncline, which is a foreland basin formed due to early Mesozoic crustal shortening. In addition, MIA suggests that during middle Jurassic time, weathering intensity in the source area of Nariinsukhait sandstone was relatively high, probably due to warm and humid climate.